Tissue Bioengineering in the Treatment of Osteochondritis Dissecans of the Talus in Children With Open Physis: Preliminary Results. Issue 7 (August 2018) - Pagliazzi, Gherardo; Baldassarri, Matteo; Perazzo, Luca; Vannini, Francesca; Castagnini, Francesco; Buda, Roberto
Abstract : Background: Juvenile osteochondritis dissecans of the talus (JOCDT) is a focal idiopathic lesion primarily of the subchondral bone leading to subsequent cartilaginous damage. The majority of the papers dealing with JOCDT reported heterogeneous case studies of patients treated with different cartilage repair techniques. The purpose of this paper is to retrospectively review both clinical and radiologic results among 7 patients affected by JOCDT treated with arthroscopic bone marrow aspirate concentrate (BMAC) transplantation with the 1-step technique. Methods: Both standard anterior-posterior and lateral radiographs and a 1.5 T magnetic resonance imaging of the affected ankle were preoperatively performed in all the patients. The American Orthopaedic Foot and Ankle Society (AOFAS) score and the visual analogue scale were administered to the patients preoperatively and at the final follow-up. Results: Patients were followed up to an average of 48.1±18.4 months. According to the Berndt and Harty classification, 6 lesions were found to be in stage III and 1 lesion in stage IV. The average preoperative AOFAS score was 58.8±7.6 points. At the mean follow-up of 48.1 months the average AOFAS score improved to 95.7±5.4 points ( P <0.05). Visual analogue scale improved from 6.3 preoperatively to 0.4 at final follow-up ( P <0.05). Complete radiographic healing, in terms of complete bony filling, was observed in 3 of 7 cases. The magnetic resonance imaging analysis showed a complete filling of the osteochondral defect in 4 patients, whereas in 1 patient a hypotrofic tissue was observed. Conclusions: BMAC transplantation is able to provide good to excellent results in the treatment of JOCDT. The 43% of our patients showed a complete radiographic healing, but all the patients were satisfied with the procedure. Because of the rareness of the lesion, further studies involving more patients and with a longer follow-up are required, to establish the advantage of performing a regenerative procedure like the BMAC transplantation in a pediatric population. Level of Evidence: Level IV.